Electrode material and preparation method thereof
By growing nitrogen-doped carbon nanotubes on the surface of foam nickel and purifying water vapor, the problem of low energy density of existing supercapacitors is solved, and the preparation of high-energy density electrode materials is realized, and the electrochemical performance of the electrode materials is improved.
Patent Information
- Application Number
- CN202311247131.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-03-28
AI Technical Summary
The low energy density of existing supercapacitors leads to performance limitations in practical applications, and it is necessary to develop electrode materials with high energy density to improve the performance of supercapacitors.
The catalytic chemical vapor deposition method is used to grow nitrogen-doped carbon nanotubes on the surface of foam nickel, and the structure of the electrode material is optimized through water vapor purification, thereby improving the electrochemical performance of the electrode material.
Through this method, the contact resistance between the active substance and the current collector is reduced, the electrochemical performance of the electrode material is improved, the preparation process is simplified, and the specific capacity per unit mass of active substance is increased.
Smart Images

Figure CN119724954A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of carbon nanotube preparation and application, and in particular relates to an electrode material and a preparation method thereof. Background Art
[0002] Supercapacitors, also known as electrochemical capacitors, are a new type of green energy storage device between traditional capacitors and secondary batteries. They have the characteristics of high power density, short charging time, long service life, wide operating temperature range, safety, and pollution-free. They have broad application prospects in many fields such as electric vehicles, aerospace, energy storage, and industrial energy-saving systems.
[0003] Supercapacitors usually consist of four components: dual electrodes, electrolytes, current collectors, and separators. The electrochemical activity of the electrode surface is the most critical part of the entire supercapacitor. The characteristics of the electrode material largely determine the performance and application prospects of the supercapacitor. The current collector and the active material bonded to the current collector are important components of the supercapacitor electrode, and their functions are to support the active material and collect the current. A good current collector usually has good conductivity, pressure resistance, and large load capacity. It usually uses stable mesh structure metals such as Cu, Ni, Al, and Ti. Activated carbon has a high specific surface area and high electrochemical stability, and is currently the most widely used electrode material.
[0004] Existing supercapacitors are subject to some limitations in practical applications due to their low energy density. How to improve the specific capacitance and energy density of supercapacitors has become an urgent problem to be solved. The electrode material in supercapacitors has a great influence on the performance of energy storage devices, so it is necessary to research and develop an electrode material with high energy density. Summary of the invention
[0005] In order to overcome the defects of the above-mentioned prior art, the purpose of the present invention is to provide an electrode material and a preparation method thereof. By selecting nickel foam as a current collector and depositing carbon nanotube active materials on the surface of the nickel foam, the preparation procedure can be effectively simplified and the electrode performance can be improved.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing an electrode material, characterized by comprising:
[0008] The nickel foam is placed in a reactor, and the atmosphere in the reactor is replaced with a protective atmosphere;
[0009] The nitrogen-containing compound and the first deionized water are introduced into the reactor at the same time, and the temperature is heated to 600-700° C. at a heating rate of 15-100° C. / s and maintained at the temperature for 30-40 minutes to in-situ grow nitrogen-doped nano-carbon materials on the porous surface of the nickel foam;
[0010] The second deionized water is used to perform water vapor purification on the foamed nickel grown with nitrogen-doped nano-carbon material to obtain a nitrogen-doped carbon nanotube / foamed nickel electrode material.
[0011] In some embodiments of the present invention, the nickel foam is a conductive nickel foam material that has been cleaned with ethanol or acetone.
[0012] In some embodiments of the present invention, the protective atmosphere is formed by one of nitrogen, helium or argon.
[0013] In some embodiments of the present invention, the nitrogen-containing compound is a liquid organic compound having a carbon-nitrogen bond, including alkanes and / or alkenes and / or aromatic hydrocarbons and / or halogenated hydrocarbons in which one or more carbon atoms are replaced by nitrogen atoms.
[0014] In some embodiments of the present invention, the nitrogen content of the nitrogen-containing compound is 3-30 wt %, and the carbon content is 25-65 wt %.
[0015] In some embodiments of the present invention, the nitrogen-containing compound and deionized water are introduced into the reactor simultaneously, comprising:
[0016] The addition rate of the nitrogen-containing compound is controlled to be 0.02-0.08 mL / min, the addition rate of the first deionized water is controlled to be 0.01-0.2 mL / min, and the mass ratio of the first deionized water to the carbon element in the nitrogen-containing compound is 1-4:1.
[0017] In some embodiments of the present invention, the parameters of water vapor purification include: purification temperature of 500-600° C., addition rate of the second deionized water of 0.01-0.1 mL / min, and purification time of 10-20 min.
[0018] In a second aspect, the present invention discloses an electrode material prepared by the above method.
[0019] In some embodiments of the present invention, the electrode material includes nickel foam and nitrogen-doped carbon nanotubes grown on the nickel foam, the diameter of the nitrogen-doped carbon nanotubes is 1-20 nm, and the mass of the nitrogen-doped carbon nanotubes is 10-50% of the mass of the nickel foam substrate.
[0020] In a third aspect, the present invention discloses a supercapacitor, wherein the electrode of the supercapacitor is made of the above-mentioned electrode material.
[0021] Technical effects and advantages of the present invention:
[0022] 1. The present invention adopts catalytic chemical vapor deposition to grow nitrogen-doped carbon nanotubes on nickel foam, thereby preparing nitrogen-doped carbon nanotube / nickel foam high-performance electrode materials, reducing the contact resistance between the active material and the current collector, improving the electrochemical properties of the electrode material, and simplifying the preparation method of the electrode material.
[0023] 2. The present invention purifies the nickel foam on which nitrogen-doped carbon nanotubes are grown by water vapor, and by optimizing the water vapor content and reaction temperature during the purification process, increases the proportion of carbon nanotubes in carbon deposits, thereby increasing the specific capacity per unit active substance mass of the nickel foam electrode material.
[0024] 3. The present invention uses nitrogen-containing compounds as precursors to ensure continuous and stable preparation of electrode materials. The prepared electrode materials have better electrochemical properties, and the difference in electrochemical properties of each batch is small.
[0025] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a flow chart of a method for preparing an electrode material of the present invention;
[0027] Figure 2 This is a SEM image of the electrode material prepared in Example 1;
[0028] Figure 3 The CV curve diagram of the electrochemical performance of the electrode material prepared in Example 1 before and after purification at a scanning rate of 50 mV / s;
[0029] Figure 4 This is a SEM image of the electrode material prepared in Comparative Example 1;
[0030] Figure 5 This is the SEM image of the electrode material prepared in Comparative Example 2. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] like Figure 1 As shown, the present invention provides a method for preparing an electrode material, comprising:
[0033] The nickel foam is placed in a reactor, and the atmosphere in the reactor is replaced with a protective atmosphere;
[0034] The nitrogen-containing compound and the first deionized water are introduced into the reactor at the same time, and the temperature is heated to 600-700° C. at a heating rate of 15-100° C. / s and maintained at the temperature for 30-40 minutes to in-situ grow nitrogen-doped nano-carbon materials on the porous surface of the nickel foam;
[0035] The second deionized water is used to perform water vapor purification on the foamed nickel grown with nitrogen-doped nano-carbon material to obtain a nitrogen-doped carbon nanotube / foamed nickel electrode material.
[0036] In some embodiments of the present invention, the nickel foam is a conductive nickel foam material cleaned with ethanol or acetone.
[0037] In some embodiments of the present invention, the protective atmosphere is formed by one of nitrogen, helium or argon.
[0038] In some embodiments of the present invention, the nitrogen-containing compound is a liquid organic compound having a carbon-nitrogen bond, including alkanes and / or alkenes and / or aromatic hydrocarbons and / or halogenated hydrocarbons in which one or more carbon atoms are replaced by nitrogen atoms.
[0039] In some embodiments of the present invention, the nitrogen content of the nitrogen-containing compound is 3-30 wt %, and the carbon content is 25-65 wt %.
[0040] In some embodiments of the present invention, the nitrogen-containing compound and deionized water are introduced into the reactor simultaneously, comprising:
[0041] The addition rate of the nitrogen-containing compound is controlled to be 0.02-0.08 mL / min, the addition rate of the first deionized water is controlled to be 0.01-0.2 mL / min, the mass ratio of the first deionized water to the carbon element in the nitrogen-containing compound is 1-4:1, and the nitrogen-containing compound and the first deionized water can be continuously injected into the reactor through a pressurized syringe.
[0042] In some embodiments of the present invention, the parameters of water vapor purification include: a purification temperature of 500-600°C, an addition rate of the second deionized water of 0.01-0.1 mL / min, and a purification time of 10-20 min. Too little water vapor content will result in more amorphous carbon deposition, affecting the electrochemical performance, while too much water vapor content will cause the carbon nanotubes to be consumed too quickly, reducing the electrochemical performance of the nickel foam after the purification reaction. Controlling the appropriate second deionized water addition rate and purification temperature can ensure a high proportion of carbon nanotubes in the carbon deposits and expand the specific capacity per unit active substance mass of the nickel foam electrode material after purification.
[0043] In a second aspect, the present invention discloses an electrode material prepared by the above method.
[0044] In some embodiments of the present invention, the electrode material includes nickel foam and nitrogen-doped carbon nanotubes grown on the nickel foam, the diameter of the nitrogen-doped carbon nanotubes is 1-20 nm, and the mass of the nitrogen-doped carbon nanotubes is 10-50% of the mass of the nickel foam.
[0045] In a third aspect, the present invention discloses a supercapacitor, wherein the electrode of the supercapacitor is made of the above-mentioned electrode material.
[0046] In order to better illustrate the present invention, the following examples and comparative examples are provided.
[0047] Example 1
[0048] S1: The nickel foam material is washed with 2 mol / L hydrochloric acid, acetone and deionized water for 10 minutes in sequence, and then reduced with hydrogen for 60 minutes to obtain the nickel foam to be reacted. The nickel foam is placed in a reactor, and the reactor is replaced with a protective atmosphere, and nitrogen is selected as the inert gas in the reactor.
[0049] S2: Pyrrole is selected as the nitrogen-containing compound, the mass ratio of the first deionized water to the carbon element is 2:1, the rate of the first deionized water is 0.01-0.2 mL / min, the rate of the nitrogen-containing compound is 0.02-0.08 mL / min, the heating rate is 15-100°C / s, the reaction temperature is 600°C, and the reaction time is 30 minutes.
[0050] S3: After the reaction is completed, stop introducing pyrrole, adjust the temperature in the reactor to 550°C, introduce a second deionized water at a rate of 0.01-0.1 mL / min, the mass of the second deionized water is 1 / 150 of the first deionized water, and the purification time is 10 minutes.
[0051] The SEM image of the electrode material prepared in this embodiment is as follows: Figure 2 As shown, the carbon nanotubes are relatively obvious and uniform, with a tube diameter of about 2-20 nanometers. The electrochemical performance of the prepared electrode material before and after the purification reaction was tested, and the electrochemical performance CV curve at a scanning rate of 50mV / s was obtained as shown in Figure 3 As shown, the charge and discharge capacity is calculated by integrating the CV curve. It can be seen that the charge and discharge capacity of the electrode material prepared in this embodiment after purification is twice that before purification and is 20 times that of the unreacted nickel foam.
[0052] Comparative Example 1
[0053] S1: The nickel foam material is washed with 2 mol / L hydrochloric acid, acetone and deionized water for 10 minutes in sequence, and then reduced with hydrogen for 60 minutes to obtain the nickel foam to be reacted. The nickel foam is placed in a reactor, and the reactor is replaced with a protective atmosphere, and nitrogen is selected as the inert gas in the reactor.
[0054] S2: Pyrrole is selected as the nitrogen-containing compound, the mass ratio of the first deionized water to the carbon element is 2:1, the rate of the first deionized water is 0.01-0.2 mL / min, the rate of the nitrogen-containing compound is 0.02-0.08 mL / min, the heating rate is 15-100°C / s, the reaction temperature is 600°C, the reaction time is 30 minutes, and no steam purification reaction is performed after the reaction is completed.
[0055] The SEM image of the electrode material prepared in this comparative example is as follows Figure 4 As shown, there is a large amount of obvious amorphous carbon on the surface, and the diameter of the carbon nanotubes is above 50nm. The charge and discharge capacity of the prepared electrode material is 10 times that of the unreacted nickel foam.
[0056] Example 2
[0057] S1: The nickel foam material is washed with 2 mol / L hydrochloric acid, acetone and deionized water for 10 minutes in sequence, and then reduced with hydrogen for 60 minutes to obtain the nickel foam to be reacted. The nickel foam is placed in a reactor, and the reactor is replaced with a protective atmosphere, and nitrogen is selected as the inert gas in the reactor.
[0058] S2: acetonitrile is selected as the nitrogen-containing compound, the mass ratio of the first deionized water to the carbon element is 1:1, the rate of the first deionized water is 0.01-0.2 mL / min, the rate of the nitrogen-containing compound is 0.02-0.08 mL / min, the heating rate is 15-100°C / s, the reaction temperature is 700°C, and the reaction time is 30 minutes.
[0059] S3: After the reaction is completed, stop introducing acetonitrile, adjust the temperature in the reactor to 600°C, introduce a second deionized water at a rate of 0.01-0.1 mL / min, the mass of the second deionized water introduced is 1 / 100 of the first deionized water, and the purification time is 20 minutes.
[0060] The diameter of the purified carbon nanotubes of the electrode material prepared in this embodiment is 10-20 nm, and the charge and discharge capacity is 16 times that of the unreacted nickel foam.
[0061] Comparative Example 2
[0062] S1: The nickel foam material is washed with 2 mol / L hydrochloric acid, acetone and deionized water for 10 minutes in sequence, and then reduced with hydrogen for 60 minutes to obtain the nickel foam to be reacted. The nickel foam is placed in a reactor, and the reactor is replaced with a protective atmosphere, and nitrogen is selected as the inert gas in the reactor.
[0063] S2: Select nitrogen-free methanol as the precursor, the mass ratio of the first deionized water to the carbon element is 2:1, the rate of the first deionized water is 0.01-0.2 mL / min, the rate of the methanol is 0.02-0.08 mL / min, the heating rate is 15-100°C / s, the reaction temperature is 600°C, and the reaction time is 30 minutes.
[0064] S3: After the reaction is completed, stop introducing methanol, adjust the temperature in the reactor to 550°C, introduce a second deionized water at a rate of 0.01-0.1 mL / min, the mass of the second deionized water is 1 / 150 of the first deionized water, and the purification time is 10 minutes.
[0065] The SEM image of the purified electrode material obtained in this comparative example is as follows: Figure 5 As shown, there are only some carbon nanotubes with short tube length, large tube diameter (greater than 15nm) and small overall mass on the surface. The charge and discharge capacity of the purified electrode material is 8 times that of the unreacted nickel foam, indicating that nitrogen doping promotes the electrochemical properties of the nickel foam electrode material.
[0066] Example 3
[0067] S1: The nickel foam material is washed with 2 mol / L hydrochloric acid, acetone and deionized water for 10 minutes in sequence, and then reduced with hydrogen for 60 minutes to obtain the nickel foam to be reacted. The nickel foam is placed in a reactor, and the reactor is replaced with a protective atmosphere, and nitrogen is selected as the inert gas in the reactor.
[0068] S2: A mixture of acetonitrile, pyrrole and methanol with a nitrogen content of 5%wt is selected as the nitrogen-containing compound, the mass ratio of the first deionized water to the carbon element is 1:1, the rate of the first deionized water is 0.01-0.2mL / min, the rate of the nitrogen-containing compound is 0.02-0.08mL / min, the heating rate is 15-100℃ / s, the reaction temperature is 700℃, and the reaction time is 40 minutes.
[0069] S3: After the reaction is completed, stop introducing the nitrogen-containing compound, adjust the temperature in the reactor to 500°C, introduce a second deionized water at a rate of 0.01-0.1 mL / min, the mass of the second deionized water introduced is 1 / 200 of the first deionized water, and the purification time is 15 minutes.
[0070] In the purified electrode material prepared in this embodiment, the diameter of the carbon nanotubes is 15-40 nm, and the charge and discharge capacity of the purified electrode material is 11 times that of the unreacted nickel foam.
[0071] In summary, the present invention adopts catalytic chemical vapor deposition to grow nitrogen-doped carbon nanotubes on nickel foam, thereby preparing nitrogen-doped carbon nanotube / nickel foam high-performance electrode materials, reducing the contact resistance between the active substance and the current collector, improving the electrochemical properties of the electrode material, and simplifying the preparation method of the electrode material. Furthermore, the present invention purifies the nickel foam on which nitrogen-doped carbon nanotubes are grown by water vapor, optimizes the water vapor content and reaction temperature during the purification process, increases the proportion of carbon nanotubes in carbon deposits, and thereby increases the specific capacity per unit active substance mass of the nickel foam electrode material.
[0072] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an electrode material, characterized in that: include: The nickel foam is placed in a reactor, and the atmosphere in the reactor is replaced with a protective atmosphere; The nitrogen-containing compound and the first deionized water are introduced into the reactor at the same time, and the temperature is heated to 600-700° C. at a heating rate of 15-100° C. / s and maintained at the temperature for 30-40 minutes to in-situ grow nitrogen-doped nano-carbon materials on the porous surface of the nickel foam; The second deionized water is used to perform water vapor purification on the nickel foam on which the nitrogen-doped nano-carbon material is grown, to obtain a nitrogen-doped carbon nanotube / nickel foam electrode material.
2. The preparation method according to claim 1, characterized in that: The nickel foam is a conductive nickel foam material that has been cleaned with ethanol or acetone.
3. The preparation method according to claim 1, characterized in that: The protective atmosphere is formed by one of nitrogen, helium or argon.
4. The preparation method according to claim 1, characterized in that: The nitrogen-containing compound is a liquid organic compound having a carbon-nitrogen bond, including an alkane and / or alkene and / or aromatic hydrocarbon and / or halogenated hydrocarbon compound in which one or more carbon atoms are replaced by a nitrogen atom.
5. The preparation method according to claim 4, characterized in that: The nitrogen content of the nitrogen-containing compound is 3-30 wt %, and the carbon content is 25-65 wt %.
6. The preparation method according to claim 1, characterized in that: The method of simultaneously introducing the nitrogen-containing compound and deionized water into the reactor comprises: The addition rate of the nitrogen-containing compound is controlled to be 0.02-0.08 mL / min, the addition rate of the first deionized water is controlled to be 0.01-0.2 mL / min, and the mass ratio of the first deionized water to the carbon element in the nitrogen-containing compound is 1-4:
1.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The parameters of water vapor purification include: purification temperature of 500-600° C., addition rate of the second deionized water of 0.01-0.1 mL / min, and purification time of 10-20 min.
8. An electrode material, characterized in that: The electrode material is prepared by the method according to any one of claims 1 to 7.
9. An electrode material according to claim 8, characterized in that: The electrode material comprises foamed nickel and nitrogen-doped carbon nanotubes grown on the foamed nickel. The diameter of the nitrogen-doped carbon nanotubes is 1-20 nm, and the mass of the nitrogen-doped carbon nanotubes is 10-50% of the mass of the foamed nickel matrix.
10. A supercapacitor, characterized in that: The electrode of the supercapacitor is made of the electrode material according to claim 8 or 9.